The Principle of Justice in Family Livelihood under Islamic Law as a Model for Employee Compensation Management - Didit Darmawan; Muhammad Alfian Dwi Prawira (Civiliza Publishing, 2026)
This study constructs a theoretical model of employee compensation management based on the principle of justice in family livelihood relations according to Islamic family law. The research employs a qualitative literature study design without field data collection. The analysis reveals five main pillars of justice derived from family livelihood: continuity of moral obligation, proportionality between burden and compensation, flexibility adjusted to the giver’s capacity, selective transparency to build trust, and special protection for weaker parties. These pillars are transformed into a compensation management framework that differs from conventional transactional models. The proposed model emphasizes that the employer employee relationship carries a moral duty similar to the husband’s obligation to provide family livelihood. Justice is achieved not through uniform wages but through proportional responses to varying needs and capacities. This framework offers theoretical contributions to human resource management and practical guidance for designing fair, sustainable compensation systems.